Pengaruh Kombinasi Vermikompos dan Vermiwash Terhadap Pertumbuhan dan Hasil Tanaman Sawi Pakcoy (Brassica rapa L.) - Mochamad Irvan Syahroni; Istirochah Pujiwati; Siti Asmaniyah Mardiyani (AGRONISMA, 2021)
Sawi is a type of vegetable that is liked by many people with a high nutritional content. Of the various types of mustard greens, pakcoy is the type that is widely cultivated. Pakcoy is a plant that contains various nutrients in the form of calories, protein, fat, carbohydrates, fiber, Ca, P, Fe, as well as vitamins A, B, C and E. This study aims to test the combination of vermicompost and vermiwash on the growth and yield of pakcoy plants good and optimum. This study used a randomized block design consisting of 2 factors. The first factor consists of Factor I, which is the vermicompost dose consisting of three levels, namely V1 = 100 g/pot, V2 = 200 g/pot, V3 = 300 g/pot. The second factor is the Vermiwash concentration consisting of three levels, namely K1 = 100 ml/liter, K2 = 200 ml/liter, K3 = 300 ml/liter, plus one control treatment using inorganic fertilizers. Each treatment combination was repeated nine times and each replication used four plant samples. The results showed that the combination of vermicompost and vermiwash had a significant effect on the growth of plant height, number of leaves and leaf area. The variable results show that the 200 g vermicompost treatment and 200 ml/l vermiwash concentrations give the same good results as 300 g vermicompost and 300 ml / l vermiwash concentrations, but the 100 g vermicompost and 300 ml/l vermiwash treatments give high results. amounting to 68.50 g. That the application of vermicompost and vermiwash doses is still not able to provide nutrients like inorganic fertilizers.Â